Relationship among welding defects with convection and material flow dynamic considering principal forces in plasma arc welding - Nguyen, Huu Loc; Nguyen, Van Anh; Duy, Han Le; Nguyen, Thanh-Hai; Tashiro, Shinichi; Tanaka, Manabu (MDPI, 2021)
The material flow dynamic and velocity distribution on the melted domain surface play a crucial role on the joint quality and formation of welding defects. In this study, authors investigated the effects of the low and high currents of plasma arc welding on the material flow and thermodynamics of molten pool and its relationship to the welding defects. The high-speed video camera (HSVC) was used to observe the convection of the melted domain and welded-joint appearance. Furthermore, to consider the Marangoni force activation, the temperature on the melted domain was measured by a thermal HSVC. The results revealed that the velocity distribution on the weld pool surface was higher than that inside the molten weld pool. Moreover, in the case of 80 A welding current, the convection speed of molten was faster than that in other cases (120 A and 160 A). The serious undercut and humping could be seen on the top surface (upper side) and unstable weld bead was visualized on the back side (bottom surface). In the case of 160 A welding current, the convection on the weld pool surface was much more complex in comparison with 80 A and 120 A cases. The excessive convex defect at the bottom side and the concave defect at the top surface were observed. In the case of 120 A welding current, two convection patterns with the main flow in the backward direction were seen. Almost no welding defect could be found. The interaction between the shear force and Marangoni force played a solid state on the convection and heat transportation processes in the plasma arc welding process.
Keywords: welding current; velocity distribution; material flow; thermodynamic; plasma arc welding